STYK1 promotes autophagy through enhancing the assembly of autophagy-specific class III phosphatidylinositol 3-kinase complex I - Zhou, Cefan; Qian, Xuehong; Hu, Miao; Zhang, Rui; Liu, Nanxi; Huang, Yuan; Yang, Jing; Zhang, Juan; Bai, Hua; Yang, Yuyan; Wang, Yefu; Ali, Declan; et al. (Autophagy, 2020)
Macroautophagy/autophagy plays key roles in development, oncogenesis, and cardiovascular and metabolic diseases. Autophagy-specific class III phosphatidylinositol 3-kinase complex I (PtdIns3K-C1) is essential for autophagosome formation. However, the regulation of this complex formation requires further investigation. Here, we discovered that STYK1 (serine/threonine/tyrosine kinase 1), a member of the receptor tyrosine kinases (RTKs) family, is a new upstream regulator of autophagy. We discovered that STYK1 facilitated autophagosome formation in human cells and zebrafish, which was characterized by elevated LC3-II and lowered SQSTM1/p62 levels and increased puncta formation by several marker proteins, such as ATG14, WIPI1, and ZFYVE1. Moreover, we observed that STYK1 directly binds to the PtdIns3K-C1 complex as a homodimer. The binding with this complex was promoted by Tyr191 phosphorylation, by means of which the kinase activity of STYK1 was elevated. We also demonstrated that STYK1 elevated the serine phosphorylation of BECN1, thereby decreasing the interaction between BECN1 and BCL2. Furthermore, we found that STYK1 preferentially facilitated the assembly of the PtdIns3K-C1 complex and was required for PtdIns3K-C1 complex kinase activity. Taken together, our findings provide new insights into autophagy induction and reveal evidence of novel crosstalk between the components of RTK signaling and autophagy. Abbreviations: AICAR: 5-aminoimidazole-4-carboxamide ribonucleotide; AMPK: adenosine 5'-monophosphate (AMP)-activated protein kinase; ATG: autophagy related; ATP: adenosine triphosphate; BCL2: BCL2 apoptosis regulator; BECN1: beclin 1; Bre A: brefeldin A; Co-IP: co-immunoprecipitation; CRISPR: clustered regularly interspaced short palindromic repeats; DAPI: 4′,6-diamidino-2-phenylindole; EBSS: Earle's balanced salt solution; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GFP: green fluorescent protein; GSEA: gene set enrichment analysis; MAP1LC3/LC3, microtubule associated protein 1 light chain 3; MAPK8/JNK1: mitogen-activated protein kinase 8; mRFP: monomeric red fluorescent protein; MTOR: mechanistic target of rapamycin kinase; MTT: 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide; PIK3C3: phosphatidylinositol 3-kinase catalytic subunit type 3; PIK3R4: phosphoinositide-3-kinase regulatory subunit 4; qRT-PCR: quantitative reverse transcription PCR; RACK1: receptor for activated C kinase 1; RUBCN: rubicon autophagy regulator; siRNA: small interfering RNA; SQSTM1: sequestosome 1; STYK1/NOK: serine/threonine/tyrosine kinase 1; TCGA: The Cancer Genome Atlas; Ub: ubiquitin; ULK1: unc-51 like autophagy activating kinase 1; UVRAG: UV radiation resistance associated; WIPI1: WD repeat domain, phosphoinositide interacting 1; ZFYVE1: zinc finger FYVE-type containing 1